OPTIMASI KOMBINASI EKSTRAK BUAH MENGKUDU (Morinda citrifolia L) DAN DAUN MAHKOTA DEWA (Phaleria macrocarpa (Scheff) Boerl.) PADA FORMULA SABUN TRANSPARAN DENGAN METODE FACTORIAL DESIGN - Intan Martha Cahyani; Bekti Nugraheni; Suwarmi Suwarmi (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACT Extracts of mengkudu fruit and mahkota dewa leaf each contain compounds that can be efficacious antibacterial Staphylococcus Aureus (acne-causing bacteria), but at high concentrations. The combination of both is expected to improve the efficiency and effectiveness of the use if the dosage form is formulated in a transparent soap. Selection of dosage forms based on a transparent soap acceptabilitas reasons. This study aims to determine the effect of the use of each and interactions extract of mengkudu fruit and mahkota dewa leaf in diameter clear zone antibacterial activity test by the method of pitting and dilution method with a parameter number of colony can then be determined comparison of the two extracts were having antibacterial activity optimum. The test results stated good use of each and combinations can enhance the clear zone according to the equation Y = 0.811 + 0.011 + 0.007 B + A 1.56. 10-5 AB, the parameters of the number of colonies also give the same result Y = 42.781 to 0.316 A - 0.228 0.006 A B + B. Optimal combination obtained extract concentration of 30% mengkudu fruit extract and 40% mahkota dewa leaf extract. Test the antibacterial activity of a combination of transparent soap mengkudu fruit and mahkota dewa leaf extracts with an optimal combination produces a clear zone diameter of 2.509 cm. Keywords : extracts of mengkudu fruit, extract of mahkota dewa, Optimization, transparent soap.